Reliability based inspection planning of offshore structures - Onoufriou, Toula (My University, 1999)
This paper presents a series of studies on the development and application of reliability based inspection planning techniques for offshore structures including fixed and floating platforms and jack-up drilling rigs. The general methodology is presented which broadly applies to all three types of offshore structure and differences between the characteristics of the various structures which need to be reflected in the detailed methodology are highlighted in the paper. The need for using these techniques is discussed together with the benefits achieved from their application. Case studies are presented to demonstrate the application and benefits of these techniques and important trends are highlighted through the results of parametric sensitivity studies. Furthermore, areas where more work is required to advance these applications further are also identified and discussed.
Keywords: Offshore structures; Reliability